MENEMUKAN POTENSI FLIPPED CLASSROOM DAN KUMON (FLICKU) : ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN FLICKU DALAM MENINGKATKAN HASIL BELAJAR IPAS MATERI ENERGI TERBARUKAN KELAS X SMA - Perdana Miftachul Hudaa Samsudin; Ishafit (STKIP Subang, 2024)
Improving the quality of life and managing human resources is an important goal of education. One strategy to improve the quality of education is to use effective learning models. This research aims to find the potential of learning models in improving learning outcomes in renewable energy material. A quantitative research design was chosen for this study. As a result, data obtained increased the average score of cognitive learning outcomes from 1.77 to 3.18.